Can the storage effect hypothesis explain weed co‐existence on the Broadbalk long‐term fertiliser experiment?. (30th June 2014) - García De León, D; Storkey, J; Moss, S R; González‐Andújar, J L; Clements, David
Summary Understanding how plant species with similar resource requirements co‐exist has been a long‐standing ecological question with several theoretical explanations. One potential mechanism is the storage effect hypothesis. According to this hypothesis, species co‐exist because they differ in when they are most actively using resource and, therefore, respond differently to environmental perturbation. The hypothesis is based on two main assumptions: (i) two competitors have different responses to climate and (ii) the responses to climate are mediated by changes in the relative importance of intra‐ and interspecific competition. The hypothesis could provide useful insights into the role of climate in maintaining weed species diversity and potential shifts in dominant species under climate change. This study tested the basic principles of the storage effect hypothesis on weed communities using data from the Broadbalk long‐term fertiliser experiment. Relative abundance of weeds in 10 plots with contrasting fertility but no herbicides was assessed for 21 years. Multivariate analyses and generalised additive mixed models were used to analyse the data. The following pairs of species were found to be adapted to similar fertiliser levels, but diverged in their response to climate: (i) Papaver rhoeas–Tripleurospermum inodorum, (ii) Medicago lupulina–Vicia sativa and (iii) Scandix pecten‐veneris–Ranunculus arvensis. Contrasting responses to spring temperature within these species pairs modified the competition balance providing evidence for the storage effect hypothesis and helping to explain weed co‐existence in the Broadbalk experiment.